Physico-chemical, Spectral and Thermal Characterization of Shilajit, A Humic Substance with Medicinal Properties† - P. AGARWAL, SURAJ; KHANNA, RAJESH; KARMARKAR, RITESH; KHALID ANWER, MD.; K. KHAR, ROOP (Asian Journal of Chemistry, 2010)
In the present study, shilajit samples from various sources were characterized based on their physico-chemical properties, UV, FTIR and 1H NMR spectra, X-ray diffraction pattern and DSC thermograms. All the samples showed a distinct similarity with respect to their physico-chemical as well as spectral and thermal characteristics. Being natural in origin, some variation can be expected and was seen in these samples too. The studies confirmed the complex multicomponent and humic nature of shilajit.